Postoperative Arrhythmia Repair of Tetralogy of Fallot in Pediatrics - Santoso, Febrina Mustika; Prishanti, Nadira; Rahma, Naswa Arvieda; Abdullah, Mokhammad Faisol; Kusumaningrat, Dorothea Respa (PT Inovasi Pratama Internasional, 2023)
Tetralogy of Fallot (ToF) is the most common cyanotic congenital heart disease. ToF affects 3% to 10% of all babies born with congenital heart disease. Arrhythmia is a common complication following congenital heart surgery. As a medical guide, it is important to know Arrhythmia as a complication after ToF surgery. Method : The author searched, selected, and chose journals related to Arrhythmia after ToF repair surgery through several research databases including ScienceDirect, Google Scholar, PubMed, and Wiley. by using the keywords